(untitled) (Global Journal of Science Frontier Research, 2020)
The process of assimilation of Cu by chromium-resistant bacteria (Arthrobacter globiformis 151B) and the influence of high-concentration Ca ions on this process have been studied in the article. The bacteria are known for their property to assimilate intensively the hexavalent chromium [Cr(VI)] ions from the environment, to convert them into trivalent form [Cr(III)] and to accumulate it in cell. This bacterium is also characterized by the absorption of other elements from the nutrient medium. The strain of bacteria under investigation was isolated from basalt samples, taken from the places highly contaminated by Cr(VI) in Kazreti (Georgia). The solutions of the studied elements Cu and of Ca were introduced simultaneously into the nutrient medium. We studied the influence of different concentrations of Ca ions during different period of time of bacteria cultivation (17 h, 24 h, 48h, 96h, 144h) on the process of assimilation of Cu by bacteria. Ca concentration in food medium made up 100 mkg/ml, 400 mkg/ml and 1600 mkg/ml. The concentration of Cu in media was 1 mkg/ml.